2021
DOI: 10.1542/peds.2021-051076
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vaccination and Infant Influenza and Pertussis

Abstract: BACKGROUND AND OBJECTIVES Infant influenza and pertussis disease causes considerable morbidity and mortality worldwide. We examined the effectiveness of maternal influenza and pertussis vaccines in preventing these diseases in infants. METHODS This inception cohort study comprised women whose pregnancies ended between September 1, 2015, and December 31, 2017, in Victoria, Australia. Maternal vaccination status was sourced fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Poor coverage has been observed in maternal influenza and pertussis vaccination in Australia and overseas (Mohammed et al 2018;Rowe et al 2019Rowe et al , 2021Giles et al 2021). When antenatal services do not provide maternal vaccines, it places the burden on pregnant women to seek vaccinations outside of the maternity care system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor coverage has been observed in maternal influenza and pertussis vaccination in Australia and overseas (Mohammed et al 2018;Rowe et al 2019Rowe et al , 2021Giles et al 2021). When antenatal services do not provide maternal vaccines, it places the burden on pregnant women to seek vaccinations outside of the maternity care system.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza and pertussis vaccination during pregnancy prevents disease in both women (Mertz et al 2013) and their infants, particularly in the first few months of life (Amirthalingam et al 2014;Dabrera et al 2015; Australian Technical Advisory Group on Immunisation (ATAGI) 2017; Rowe et al 2021). Maternal influenza and pertussis vaccination results in a risk reduction of disease in infants <2 months old by 56% and 80%, respectively (Nunes and Madhi 2017;Rowe et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There is a gap in research looking at the impact of COVID-19 on antepartum Tdap rates; a survey conducted by the CDC found that only 55% of the women surveyed had received antepartum Tdap pre-pandemic in 2018 (Lindley et al, 2019 ). With the notable impact of COVID-19 on childhood vaccinations it is more important than ever to ensure that all pregnant women are receiving the antepartum Tdap vaccine with each pregnancy so that infants are protected from pertussis infection (Bramer et al, 2020 ; Rowe, et al, 2021 ; Santoli et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding influenza vaccination, lower coverage was reported in one study (48% v 59%, n = 71), 26 three studies reported similar coverage (49% v 50%, n = 170 683; 36 43% v 45%, n = 70 635; 35 48% v 49%, n = 1233 40 ), one study reported higher influenza vaccine coverage (54% v 41%, n = 1305), 34 while another study found overseas regional variability in coverage compared with that of Australian‐born women for influenza vaccine (46–61% v 55%, n = 249 798) 29 . In five studies, maternal pertussis vaccine coverage in women of CALD background ranged between 63% and 80%, which was predominantly lower compared with other Australian women, where coverage was 76–86% ( N = 488 731) 29,34‐36,40 . Additionally, a study that included 69% of women of CALD background reported coverage of 57% ( n = 489) and 61% ( n = 204) for influenza and pertussis vaccines, respectively 33 (Supporting Information, table 2).…”
Section: Maternal Vaccine Coverage Among Women Of Cald Backgroundmentioning
confidence: 91%